Street Gangs and Drug Sales in Pasadena and Pomona, California, 1989-1991 - Maxson, Cheryl L. ([Verlag nicht ermittelbar], 1995)
These data were collected to explore connections between street gangs and drug distribution. The research objectives for this study were (1) to assess the magnitude of gang involvement in cocaine and other drug sales in two suburban cities, (2) to compare the characteristics of gang-involved drug sale incidents with those without gang involvement, (3) to assess the generalizability of findings on cocaine to other drugs, and from urban to more suburban settings, and (4) to translate the implications of the research findings into the development of law enforcement strategies. Law enforcement arrest records and gang membership records were obtained for two study sites, Pasadena and Pomona, California. Part 1, the incident-level file, supplies information on arrest incidents qualifying as drug sales. Variables in the file include presence at arrest of violence, guns, cash, and drugs, types of charges, gang characteristics of the incident, racial/ethnic makeup of arrestees, gender of arrestees, and gang affiliation of arrestees. Part 2, the participant-level file, supplies data on each participant in each incident. Variables in this file include gender, ethnicity, gang membership status, and charges.